A Reversed Photosynthesis‐like Process for Light‐Triggered CO2 Capture, Release, and Conversion. Issue 12 (10th May 2017) - Wang, Dingguan; Liao, Shenglong; Zhang, Shiming; Wang, Yapei
Abstract: Materials for CO2 capture have been extensively exploited for climate governance and gas separation. However, their regeneration is facing the problems of high energy cost and secondary CO2 contamination. Herein, a reversed photosynthesis‐like process is proposed, in which CO2 is absorbed in darkness while being released under light illumination. The process is likely supplementary to natural photosynthesis of plants, in which, on the contrary, CO2 is released during the night. Remarkably, the material used here is able to capture 9.6 wt.% CO2 according to its active component. Repeatable CO2 capture at room temperature and release under light irradiation ensures its convenient and cost‐effective regeneration. Furthermore, CO2 released from the system is successfully converted into a stable compound in tandem with specific catalysts. Abstract : Catch, release, and convert : A light‐triggered CO2 capture, release, and conversion system is proposed. The system relies on renewable energy without the need of fossil fuel‐derived energy, and is very promising for practical applications to reduce excess CO2 . In terms of capturing CO2 during the night and releasing CO2 under light, the system is likely supplementary to the natural photosynthesis for improving the CO2 ‐conversion efficiency by natural plants.